Juridical Normative Analysis of Gig Worker Partnership Relationshio In Indonesia From The Perspektif of International Human Rights Standards - Wihadi, Susy Putri; Kurniawan, Thomas Mulyanto; Ariyanto, Alfred; Saputri, Nunuk Jati (International Journal of Law and Legal Ethics, 2025)
The growth of the sharing economy in Indonesia has shifted the traditional employment paradigm toward digital partnership schemes. However, this scheme creates legal status uncertainty, which impacts the neglect of workers' basic rights. This study aims to analyze the gap between partnership regulations in Indonesia and international Human Rights (HAM) standards regarding decent work. Using a juridical-normative method with a comparative legal approach, this study found that algorithmic control by application companies creates a subordinate relationship that is de facto an employment relationship, but lacks de jure protection. The results show violations of the right to fair wages, health insurance, and job security. This study recommends the need for a third legal category to bridge the gap in protection for gig workers.